Comparative immunosecretome analysis of prevalent Streptococcus suis serotypes. (April 2018) - Gómez-Gascón, Lidia; Luque, Inmaculada; Tarradas, Carmen; Olaya-Abril, Alfonso; Astorga, Rafael J.; Huerta, Belén; Rodríguez-Ortega, Manuel J.
Highlights: Immunoproteomics was used to identify secreted immunoreactive proteins in prevalent Streptococcus suis serotypes. Sixty-seven immunoreactive proteins were found in secretomes of the studied S. suis serotypes. Immunoreactive secreted proteins highly distributed among S. suis serotypes may be interesting for future vaccine testing. Abstract: Streptococcus suis is a major Gram-positive swine pathogen associated with a wide variety of diseases in pigs. The efforts made to develop vaccines against this pathogen have failed because of lack of common cross-reactive antigens against different serotypes. Nowadays the interest has moved to surface and secreted proteins, as they have the highest chances to raise an effective immune response because they are in direct contact with host cells and are really exposed and accessible to antibodies. In this work, we have performed a comparative immunosecretomic approach to identify a set of immunoreactive secreted proteins common to the most prevalent serotypes of S. suis . Among the 67 proteins identified, three (SSU0020, SSU0934, and SSU0215) were those predicted extracellular proteins most widely found within the studied serotypes. These immunoreactive proteins may be interesting targets for future vaccine development as they could provide possible cross-reactivity among different serotypes of this pathogen.